Implementation of Social Forestry Policy Around the Meranti Sungai Merah Protection Forest Area - Heripan Heripan; Ridhah Taqwa; Dwi Putro Priadi; Noril Milantara; Jun Harbi (Sriwijaya Journal of Environment, 2019)
One of the concrete efforts made by the Indonesian government is through social forestry policy as a trigger for land conflicts. One area that has implemented a pattern of social forestry is a forest area located in the management area of the Regional Technical Implementation Unit(UPTD) KPHRegion I Meranti located in Musi Banyuasin Regency. Only 3 social forestry scheme permits have been issued. So the aims of this study was to find out and analyze the process of implementing social forestry policy and analyze the factors that influence. The study was conducted in Pangkalan Bulian and Lubuk Bintialo Villages, Batang Hari Leko District, Musi Banyuasin Regency, South Sumatra Province. Used descriptive method combined (mixed methods) from two different approaches namely quantitative or qualitative approaches. Funding and staff resources (human resources) are still lacking. The process of collective action between actors is running well with the existence of a committed PPS Working Group. Technical rules are clear with the existence of SOPs that are derived from the rules of government and local government.Communication goes well between communities (Forest farmer groups and cooperative members) - local government and facilitators, but not so well between government structures (village heads and apparatus and local government.The Social forestry policy in Musi Banyuasin District, South Sumatra has been effectively implemented from the perspective of policy accuracy in resolving forestry problems and environmental accuracy in accepting policies.